Bed rails and endotracheal tube connectors as possible sources for spreading Acinetobacter baumannii in ventilator-associated pneumonia patients - Suphawita Chaladchalam (2018)
This study aimed to determine molecular patterns of Acinetobacter baumannii using a PCR-based technique with REP-1, REP-2 and M13 primers to distinguish the patients' strains and the environmental strains (condensate, endotracheal tube connector, bed rail and nurses hands). There were 67 cases of ventilator-associated pneumonia (VAP) among 600 patients using mechanical ventilators in 10 wards from March to July 2006. The incidence of VAP was 11.2% or 8.9/1,000 ventilator days with a 54.5% fatality rate. Among 19 of 22 A. baumannii VAP patients, 68.4% (13/19) had their environmental samples contaminated with A. baumannii and the most common contaminated sites were bed rails and endotracheal tube connectors (36.8% each). Multidrug resistant (MDR) A baumannii were involved in 77.3% of A baumannii-VAP. Molecular typing of 96 A baumannii isolates was able to differentiate A baumannii isolates into 7 types. Type 2 was the most common and found in 77.3% (17/22) of A baumannii VAP patients admitted in 6 of 7 wards. Identical fingerprints were found in clinical isolates and their bed rails, endotracheal tube connectors and condensates of 5 patients. The results demonstrate that multiple clones of MDR A baumannii were widely spread in the hospital. Bed rails and contaminated endotracheal tube connectors could be potential sources of A baumannii spread.